Examine the role Family functions, loneliness feeling and self-esteem in adolescent Internet addiction - Ali Easa Zadegan; Sohrab Amiri; Sajad Ghasem Zade (مطالعات روانشناسی تربیتی, 2017)
The aim of the present study was to drawing relationships between family functioning's predictor variables, loneliness and self-esteem with internet addiction in adolescent students. From high school students in Urmia city 390 (235 boys, 155 girls) participants were selected by a multistage cluster sampling. Then the Young's Internet Addiction Scale, Family Assessment Device (FAD) questionnaire, loneliness feeling questionnaire and Self-esteem questionnaire were distributed among the participants to respond. Ultimately, collected data were analyzed by using Enter regression analysis, multivariate analysis of variance (MANOVA), and one-way ANOVA to verify the purpose of the study. The results showed a significant correlation between family function, loneliness and self-esteem with Internet addiction (P<0/001). Tthe results of regression model also showed that in total, predictor variables explain 60% of variance of criterion variable (R2=60). Examining the gender role indicated that these variables does not have a significant proportion in predicting Internet addiction, and Analysis of variance showed a significant difference between students with Internet addiction and normal students (P<0/001) in family functioning, loneliness and self-esteem. So students with Internet addiction had lower scores in components of family functioning, loneliness and self-esteemin comparison with the normal group